2009
DOI: 10.4103/0973-1482.52785
|View full text |Cite
|
Sign up to set email alerts
|

Brain metastasis from esophageal carcinoma

Abstract: Esophageal carcinoma rarely metastasizes to brain. In our center, among 504 cases of esophageal cancer registered for treatment during a 15-year (1990-2005) period, brain metastasis from esophageal carcinoma was detected in only 1 case. An unusual case of esophageal carcinoma that presented with brain metastasis is reported here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
1
10
0
Order By: Relevance
“…In the present study, peripherally enhanced thin cyst walls (37/62, 59.7%) were more frequently observed compared to other common metastatic brain tumors. In Table 4, imaging features of brain metastases associated with esophageal carcinomas that have been published since 2004 [2,[11][12][13][14][15][16][17][18][19] are presented. In particular, cystic, enhanced tumors with minimal edema were notable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, peripherally enhanced thin cyst walls (37/62, 59.7%) were more frequently observed compared to other common metastatic brain tumors. In Table 4, imaging features of brain metastases associated with esophageal carcinomas that have been published since 2004 [2,[11][12][13][14][15][16][17][18][19] are presented. In particular, cystic, enhanced tumors with minimal edema were notable.…”
Section: Discussionmentioning
confidence: 99%
“…After computed tomography (CT) had been introduced for clinical use in the 1970s, brain metastasis from esophageal carcinoma began to be reported clinically. [5][6][7][8]11,16] However, the majority of esophageal carcinoma reports were still based on autopsies. [9,10] With the clinical application of MRI, a larger number of reports of esophageal carcinoma have been published, [2][3][4][12][13][14][15][17][18][19] although, few reports have described both MRI findings and clinical features.…”
Section: Introductionmentioning
confidence: 99%
“…However, the overall incidence of brain metastases in gastrointestinal cancers patients is relatively low [8,9,10]. Other reports that have pooled information either from several other clinical studies and autopsy studies [11] or only from autopsy series [12] have suggested that the frequency of brain metastases varies from 1 to 5% in all EC patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical outcome does not appear to be influenced by the presenting histology [34,36,41]. These rates do not differ from other BM in general [32,34,37,38]. Most patients die due to systemic disease, although patients with multiple BM tend to die due to neurological deterioration.…”
Section: Survival and Outcomementioning
confidence: 88%
“…The survival periods once PTC is diagnosed with a BM as well as its individual treatments are presented in Table 3. Table 2 Average survival periods in months following specific treatment of brain metastases originating from thyroid carcinoma [16,17,23,[115][116][117][118] [32][33][34]. In the Western population, esophageal adenocarcinomas are more frequent.…”
Section: Survival and Outcomementioning
confidence: 99%